The Correlation Between Visual, Auditory, and Kinesthetic Student's Learning Styles and Writing Skill - Mutiara Noor Imani; Fika Megawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Students study in a variety of ways or styles. Understanding and learning challenges may be impacted by this learning style. One of the numerous types of research is on learning style. Student’s learning styles and diverse learning methods might help them become better writers in English. This research aims to demonstrate how students' learning styles and the development of their writing skill are related. The participants in this research are VIII-A graders at one of the Muhammadiyah private schools in Sidoarjo. This correlation study used a Likert scale questionnaire as the instrument. The answers to the questionnaire were then connected with the students' writing scores using a quantitative research strategy and the correlation with IBM SPSS 26. The researchers found that the result of testing the hypothesis (rcount) was 0.641 and the score (rtable) was 0.515 indicating that the score of rcount>rtable was 0.641>0.515. This means that Ha is accepted and H0 is rejected which has a positive meaning or there is a significant relationship between students' visual, auditory, and kinesthetic learning styles and students' writing skill. This study implies that each student has certain learning style so that in the classroom instruction the teachers need to be aware their different characteristics to optimize the students’ learning outcomes including in English writing class